Regional cerebral metabolic levels and turnover in awake rats after acute or chronic spinal cord injury. Issue 8 (27th June 2020) - Wu, Liang; Niu, Zhanfeng; Hu, Xulei; Liu, Huili; Li, Shuang; Chen, Lei; Zheng, Danhao; Liu, Zhuang; Liu, Taotao; Xu, Fuqiang; Manyande, Anne; Wang, Jie; et al.
Abstract: Spinal cord injury (SCI) is a common cause of disability, which often leads to sensorimotor cortex dysfunction above the spinal injury site. However, the cerebral regional effects on metabolic information after SCI have been little studied. Here, adult Sprague‐Dawley rats were divided into acute and chronic treatment groups and sham groups with day‐matched periods. The Basso, Beatte, and Bresnahan scores method were utilized to evaluate the changes in behaviors during the recovery of the animals, and the metabolic information was measured with the 1 H‐observed/ 13 C‐edited NMR method. Total metabolic concentrations in every region were almost similar in both treated groups. However, the metabolic kinetics in most regions in the acute group were significantly altered ( P  < .05), particularly in the cortical area, thalamus and medulla ( P  < .01). After long‐term recovery, some metabolic kinetics were recovered, especially in the temporal cortex, occipital cortex, and medulla. The metabolic kinetic changes revealed the alteration of metabolism and neurotransmission in different brain regions after SCI, which present evidence for the alternation of brain glucose oxidation. Therefore, this shows the significant influence of SCI on cerebral function and neuroscience research. This study also provides the theoretical basis for clinical therapy after SCI, such as mitochondrial transplantation.